ANALISIS PENGARUH BUDAYA KESELAMATAN KERJA TERHADAP KEPATUHAN PENGGUNAAN ALAT PELINDUNG DIRI (APD) PEKERJA DI BAGIAN LABORATORIUM AIR PT UNILAB PERDANA JAKARTA SELATAN - Ai Silmi; Deni Kurniawan (FT-USNI, 2023)
This study aims to determine and analyze the safety culture (knowledge, attitude towards regulations, personality, availability of equipment, training, and motivation) that affect the compliance with the use of Personal Protective Equipment (PPE) of workers at the Water Laboratory of PT Unilab Perdana, South Jakarta. The research method used is quantitative with an explanatory format. The population of this study were 17 workers in the water laboratory of PT Unilab Perdana, South Jakarta. The sampling technique is a saturated sample, that is, all members of the population are used as samples. The research sample was 17 workers in the water laboratory of PT Unilab Perdana, South Jakarta. The research data collection technique used a questionnaire on compliance with the use of PPE on workers as the dependent variable and knowledge, attitude towards regulations, personality, availability of equipment, training, motivation as independent variables. Data analysis used simple correlation regression, t test, and coefficient of determination. The results showed that safety culture had a positive and significant effect on compliance with the use of PPE. The results of the t-test for tcount are greater than ttable, namely 3.493 > 2.109 at = 0.05 and 2.898 at = 0.01. This means that the correlation coefficient of safety culture on compliance with the use of PPE is significant. The coefficient of determination of the influence of safety culture on compliance with the use of PPE is obtained from the R square value of 0.449. So 44.9% of the variance in safety culture can be explained by the variable of compliance with the use of PPE. From the results of hypothesis testing, the findings show that safety culture has a positive and significant effect on compliance with the use of PPE. This means, the higher the safety culture, the higher the compliance with the use of PPE. Based on these findings, it can be concluded, if you want to improve compliance with the use of PPE, then the safety culture needs to be improved as well.